DECENTRALISATIE VAN HET ONDERWIJS AS AN EARLY STEP TO ACCULLURATION - Anugrah Pradana, Syafa’at; Magun Pikahulan, Rustam (Al-Risalah Jurnal Ilmu Syariah dan Hukum, 2021)
A lack of proper interpretation of Decentralisatie Van Het Onderwijs or education decentralization in practice has led to confusion in understanding the legal aspects of education decentralization to oversee the targeted acculturation of Indonesian citizens. Decentralisation Van Het Onderwijs, a Dutch education reform law, was the impetus for this study, which seeks to shed light on the role that decentralization plays in the process of cultural assimilation. Through an examination of the decentralization concept associated with Law No. 23 of 2014 concerning regional government, the legal meaning of education decentralization is determined. Of primary importance is creating an educational framework, which includes teaching student’s values such as morality and respect for others. This framework can only be established through a well-resourced educational system. When it comes to education, moral training, character development, and social responsibility are all part of formal education. Only traditional religious schools, such as pesantren, can provide all of this information.